Pengaruh Leverage, GCG, Profitabilitas Terhadap Harga Saham pada Sektor Makanan & Minuman di BEI Periode 2015-2018 - Lusiani Ari Ambarwati; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
The purpose of his study is to investigate the influence of leverage, outstanding corporate governance, and profitability on the share price of the food and beverage subsector. Analyzed independent variables included leverage, outstanding corporate governance, and profitability as evaluated by DER, management ownership, institutional ownership, and ROE. The population includes food and beverage subsector firms registered between 2015 and 2018. 19 companies that met the sampling conditions were chosen as samples using the technique of purposeful selection. Using approaches for panel data regression analysis, the data were evaluated. The study's findings suggest that Managerial Ownership, Institutional Ownership, and ROE have an effect on the stock price. DER has comparatively minimal effect on stock prices.